CHARACTERISTIC AND CORRELATION BETWEEN TIME AND COMPLICATION AFTER DESTRUCTIVE EYE PROCEDURE PATIENT AT PLASTIC AND RECONSTRUCTION DIVISION SANGLAH HOSPITAL’S EYE CLINIC BALI-INDONESIA - Triharpini, N; Sukartini, D; Yuliawati, P. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 6, No. 1 Januari 2012, 2012)
ABSTRACT Destructive eye procedure can be carried out by enucleation, evisceration and excenteration. Some efforts have been developed to reduce the complications, but it still occur within several years after the operation. This research aims to find out the characteristic and correlation between time and complications in patient after destructive eye procedure at Plastic and Reconstruction Division Sanglah Hospital’s Eye Clinic. For addition, characteristic of other patients in plastic and reconstruction also provided. This report is an analytical cross sectional study. Data were collected retrospectively from medical report of patients with history of destructive eye procedure in Sanglah Hospital’s eye clinic from January 1st until December 31st 2010. Patient’s characteristics were presented as frequency, percentage, mean, and standard deviation. Correlations between variables were statistically analyzed with Correlation of Lambda. Eye trauma, anophthalmic socket and nasolacrimal duct obstruction were the most common diagnosis at plastic and reconstruction division Sanglah Hospital’s eye clinic. There were 17 patients with history of destructive eye procedure in this report, including 76.5% male and 23.5% female. There is 58.8% destructive eye procedure held in age 13-50 year, mean 30.75 (SD 19.81). Infection (35.3%), trauma (23.5%) and tumor (11.8%) were the most common cause of destructive eye procedure in this study. Complications of destructive eye procedure occur in 70.6% of patient with contracted socket was the most common complication (58.3%). There was medium correlation between time and complication after the procedure, but the correlation was not statistically significant (r = 0.40; p > 0.05). In conclusion, from this study we obtained that there was medium correlation between time and complication after the procedure, but the correlation was not statistically significant.
Keywords: Destructive eye procedure, cause, complication, time